PRE-WEANING MORTALITY PATTERN OF NELLORE LAMBS IN AN ORGANIZED FARM (Indian Journal of Animal Production and Management, 2015)
The information on pre-weaning lamb mortality of Nellore Sheep was calculated from the available records and analyzed on the basis of season, month, sex and type of body system involved in diseased conditions. The results indicated that during the study period 1752 births and 110 deaths were noticed. Majority of the lambs were died during winter season (59.1%) followed by summer season (30.9%). Respiratory system (37.27%) and Digestive system (31.82%) related diseases were the main reasons of lamb mortality.
Keywords: Preweaning; mortality patterns and Nellore lambs